Volumetric and viscometric properties of amino acids in aqueous solutions of various drugs at different temperatures: A review. (16th February 2022) - Rani, Ruby; Rajput, Shikha; Sharma, Keshav; Baboria, Vikrant
Abstract : This review systematically surveys the limiting apparent molar volume, limiting apparent molar volume of transfer, Hepler's constant, hydration number, viscosity B-coefficients, and temperature derivative of B -coefficients, dB/dT of amino acids in aqueous solution of various drugs at different temperatures as these data are quite important for interpreting the hydration and other properties of proteins. The effect of drug on the volumetric and viscometric properties of amino acids has been discussed in terms of various physicochemical interactions, e.g. ion-ion, ion-hydrophilic, hydrophilic–hydrophilic, hydrophilic–hydrophobic and hydrophobic–hydrophobic interactions. These are also discussed in terms of structure-making/structure-breaking tendency of the amino acids in presence of various drugs. The comparison of these effects on the amino acid hydration enables us to have a better understanding of the influence of drugs on the protein stabilization. GRAPHICAL ABSTRACT: UF0001